TERAPI ALTERNATIF PENGURANGAN RASA NYERI DAN KECEMASAN MELALUI SLOW STROKE BACK MASSAGE (SSBM) PADA INPARTU KALA I FASE AKTIF - Diah Evawanna Anuhgera; Wilda Wahyuni Siregar; Nikmah Jalilah Ritonga; Desikawali Pardede (JURNAL KEBIDANAN KESTRA (JKK), 2020)
Abstract Labor is always synonymous with the experience of pain and fear felt by mother. SSBM stimulates the body release endorphins which are having natural pain killing propoerties and reducing anxiety levels. This study aimed to determine the effect of slow stroke back massage (SSBM) on reduction of labor pain and anxiety during first stage of labor. A quasi-experimental study with purposive non-probability sampling techniwue is used for the people. Study was conducted on 36 samples (18 in experimental group anda 18 in control group). A structured interview schedule, albor assesment performa, numerical pain rating scale and DASS(Depresssion, Anxiety and Stress Scales) were used for data collection and the data were analyzed by paired and unpaired t test. There were statistically significant differences of anxiety and pain levels before and after intervention in the experiment and control group with p value 0.00.Result confirmed that SSBM is significantly effective in reducing labor pain and anxiety level during first stage of labor. Abstract Labor is always synonymous with the experience of pain and fear felt by mother. SSBM stimulates the body release endorphins which are having natural pain killing propoerties and reducing anxiety levels. This study aimed to determine the effect of slow stroke back massage (SSBM) on reduction of labor pain and anxiety during first stage of labor. A quasi-experimental study with purposive non-probability sampling techniwue is used for the people. Study was conducted on 36 samples (18 in experimental group anda 18 in control group). A structured interview schedule, albor assesment performa, numerical pain rating scale and DASS(Depresssion, Anxiety and Stress Scales) were used for data collection and the data were analyzed by paired and unpaired t test. There were statistically significant differences of anxiety and pain levels before and after intervention in the experiment and control group with p value 0.00.Result confirmed that SSBM is significantly effective in reducing labor pain and anxiety level during first stage of labor.